Evaluating South Africa's child support grant policy : critical considerations - Hlwatika, N.R.; Raseala, P. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
The evaluation of public policies assists in ascertaining the extent to which a policy meets its objectives. The paper is conceptual in nature and aims to emphasise the significance of public policy evaluation, particularly highlighting critical considerations to be made when evaluating one of South Africa's social policies, namely, the Child Support Grant (CSG). The paper opted for a qualitative desktop study with data stemming from journal articles, books and document analysis. The paper provides conceptual insights on the significance of evaluating public policy and critical considerations to be made when evaluating the CSG. It indicates that concerning the CSG, the focus is often on implementation and impact, and there are not sufficient evaluations conducted. Furthermore, it suggests that in conducting an evaluation on the CSG, other factors from the external environment which have an influence on the uptake of the grant should be considered. The little evaluation that has been conducted on the CSG policy is outdated and therefore excludes present day conditions thus prohibiting a comprehensive and up to date evaluation of the policy. The paper adds value not only by highlighting the significance of public policy evaluation, but also the critical considerations that should be made in the process, particularly with the CSG. This is of interest not only to policy makers, but to South African citizens at large as the policy affects the national budget allocations, taxpayers, caregivers and their dependents and government in general.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Child Support Grant; Evaluation, External Environmental Factors; Public Policy; Child grant; Public policy